Arabidopsis KASH Proteins SINE1 and SINE2 Are Involved in Microtubule Reorganization During ABA-Induced Stomatal Closure - Biel, Alecia; Moser, Morgan; Meier, Iris (Frontiers in Plant Science, 2020)
Abscisic acid (ABA) induces stomatal closure by utilizing complex signaling mechanisms, allowing for sessile plants to respond rapidly to ever-changing environmental conditions. ABA regulates the activity of plasma membrane ion channels and calcium-dependent protein kinases, Ca2+ oscillations, and reactive oxygen species (ROS) concentrations. Throughout ABA-induced stomatal closure, the cytoskeleton undergoes dramatic changes that appear important for efficient closure. However, the precise role of this cytoskeletal reorganization in stomatal closure and the nature of its regulation are unknown. We have recently shown that the plant KASH proteins SINE1 and SINE2 are connected to actin organization during ABA-induced stomatal closure but their role in microtubule (MT) organization remains to be investigated. We show here that depolymerizing MTs using oryzalin can restore ABA-induced stomatal closure deficits in sine1-1 and sine2-1 mutants. GFP-MAP4-visualized MT organization is compromised in sine1-1 and sine2-1 mutants during ABA-induced stomatal closure. Loss of SINE1 or SINE2 results in loss of radially organized MT patterning in open guard cells, aberrant MT organization during stomatal closure, and an overall decrease in the number of MT filaments or bundles. Thus, SINE1 and SINE2 are necessary for establishing MT patterning and mediating changes in MT rearrangement, which is required for ABA-induced stomatal closure.